Developing a Middle-Range Theory of Heart Failure Self-Care. (April 2021) - Attaallah, Sumayya A.; Peters, Rosalind M.; Benkert, Ramona; Yarandi, Hossein; Oliver-McNeil, Sandra; Hopp, Faith
Middle-range nursing theories provide a bridge between the more abstract grand nursing theories, research, and clinical practice. As such, middle-range nursing theories derived from extant nursing theories are critical for developing and advancing both nursing science and practice. This paper describes the strategy used in developing a middle-range theory of heart failure self-care. After integrating theoretical and empirical literature, a hypothetico-deductive approach was used to develop the middle-range theory of heart failure self-care from Orem's theory of self-care. Theoretical substruction was used to provide a graphic representation of the conceptual-theoretical-empirical structure demonstrating the congruence between the theoretical and operational systems.